2022
DOI: 10.1038/s41586-022-05204-z
|View full text |Cite
|
Sign up to set email alerts
|

CDK11 regulates pre-mRNA splicing by phosphorylation of SF3B1

Abstract: RNA splicing, the process of intron removal from pre-mRNA, is essential for the regulation of gene expression. It is controlled by the spliceosome, a megadalton RNA-protein complex that assembles de novo on each pre-mRNA intron via an ordered assembly of intermediate complexes 1,2 . Spliceosome activation is a major control step requiring dramatic protein and RNA rearrangements leading to a catalytically active complex [1][2][3][4][5] . Splicing factor 3B subunit 1 (SF3B1) protein, a subunit of the U2 snRNP 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 81 publications
2
45
0
Order By: Relevance
“…Finally, we asked whether specific pharmacological targeting of other major tCDKs can also induce synthetic lethality in combination with Nutlin-3a. We targeted CDK7, CDK8, CDK11 and CDK12/13 using YKL-5–124 ( 56 ), Senexin A ( 57 ), OTS964 ( 16 , 58 ) and THZ531 ( 59 ) inhibitors, respectively, and conducted the combinatorial cytotoxicity and Bliss synergy score assays. While targeting CDK8 was not cytotoxic to HCT116 cells, inhibitors of other tCDKs showed modest cytotoxicity in the absence of Nutlin-3a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we asked whether specific pharmacological targeting of other major tCDKs can also induce synthetic lethality in combination with Nutlin-3a. We targeted CDK7, CDK8, CDK11 and CDK12/13 using YKL-5–124 ( 56 ), Senexin A ( 57 ), OTS964 ( 16 , 58 ) and THZ531 ( 59 ) inhibitors, respectively, and conducted the combinatorial cytotoxicity and Bliss synergy score assays. While targeting CDK8 was not cytotoxic to HCT116 cells, inhibitors of other tCDKs showed modest cytotoxicity in the absence of Nutlin-3a.…”
Section: Resultsmentioning
confidence: 99%
“…Another set of well-studied tCDKs includes CDK8 and its CDK19 paralogue, which bind cyclin C to influence gene expression by phosphorylating transcription factors and controlling structure and function of the Mediator ( 14 ). Finally, CDK11 binds cyclins L1 and L2 to regulate transcription and pre-mRNA splicing by phosphorylating the CTD of Pol II and the U2 small nuclear ribonucleoprotein subunit SF3B1 ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some data may help to address this question. Since previous in vitro spliceosome analyses showed that SF3B1 is phosphorylated during spliceosome activation, typically from B to B act complex (Wang et al, 1998; Shi et al, 2006; Bessonov et al, 2010; Agafonov et al, 2011; Hluchý et al, 2022), we paid attention to the phosphorylation status of SF3B1 that interacts with RBM17. Our in vitro binding assay revealed that RBM17 can bind to total SF3B1, but without SAP30BP, RBM17 does not bind well to active phosphorylated SF3B1.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that OTS964 blocks pre‐mRNA splicing in a similar manner to the splicing inhibitor pladienolide B, but via a different mechanism. 7 Pre‐mRNA splicing is performed by a spliceosome, a huge RNA‐protein complex that is progressively assembled on introns via spliceosome intermediate complexes termed E, A, B, B act , B*, C, C*. The intermediates are formed by the stepwise recruitment and release of small nuclear ribonucleoprotein particles (snRNPs) named U1, U2, U4, U5 and U6.…”
Section: Commentarymentioning
confidence: 99%